Stabilization Beyond Mood: Stabilizing Patients With Bipolar Disorder in the Various Phases of Life - Simonetti, Alessio; Koukopoulos, Alexia E.; Kotzalidis, Georgios D.; Janiri, Delfina; De Chiara, Lavinia; Janiri, Luigi; Sani, Gabriele (Frontiers in Psychiatry, 2020)
Background. There are different ways to intend stabilization and the currently main standpoint regards it as no-depression/no-mania. Furthermore, man is physiologically different from childhood to adulthood, to old age, so the meaning of stabilization should take into account growth and maturity. We aimed to review systematically studies focusing on mood stabilization in all phases of bipolar disorder (BD) and across all life phases, including pregnancy and the perinatal period, which is a still different phase in women’s life cycle. Methods. We carried out a PubMed search focusing on studies of bipolar disorder treated with drugs and aimed at stabilization with the following search strategy: stabiliz*[ti] OR stabilis*[ti] OR stable[ti] OR stability[ti]) AND mood[ti] AND bipolar. In conducting our review, we followed the PRISMA statement. Agreement on inclusion was reached by consensus of all authors through a Delphi rounds procedure. Results. The above search strategy produced 509 records on January 25, 2020. Of them, 58 fitted our inclusion criteria and were discussed. The eligible studies spanned from September 1983 to July 6, 2019. Conclusions. No clear-cut indications could be drawn due to a number of limitations involving sample inconsistency and different methods of assessing mood stabilization. The evidence as far collected does not allow to recommend treatments for children, pregnant or perinatal women, and aged patients. Adults are better focused upon. For their manic/mixed phases, second generation antipsychotic drugs may be useful in the short-to-medium run, alone or combined with mood stabilizers (MSs). However, MSs, and especially lithium, continue to be pivotal in chronic treatment. Bipolar depression should rely on MSs, but an antidepressant may be added on and prove helpful. However, there are concerns with the tendency of antidepressants to induce the opposite polarity or mood instability, rendering the need for concurrent MS prescription mandatory.